La protection sociale dans le secteur de la culture et de la création: Pratiques et innovations observées dans différents pays - Carlos Galián; Margherita Licata; Maya Stern-Plaza (Organisation internationale du Travail, 2022)
Social Protection in the culture and creative sector - this Working Paper is based on the ILO Centenary Declaration for the Future of Work, 2019, which calls on the ILO to direct its efforts to "developing and enhancing social protection systems, which are adequate, sustainable and adapted to developments in the world of work." In particular, the paper reviews policy and legal frameworks in selected countries that have pursued specific solutions to extend social security to workers in the creative and culture sector, in order to identify entry points and mechanisms for expanding coverage. Policy options ensuring the adequacy and the sustainability of such systems are discussed, taking into account particular employment circumstances in the sector, such as fluctuating employment status, irregular incomes, intermittent nature of work, and geographic mobility. The paper also situates the discussion within the COVID-19 pandemic, offering an overview of social protection measures put in place by governments in the culture and creative sector.
Keywords: 330; self employment; temporary employment; social protection; social security; service sector; entertainment industries; mass media; COVID-19